Implimentasi Surat al-Baqarah Ayat 282 Dalam Pertanggungjawaban Mesjid Di Sumatera Timur - Syahman Sitompul; N Nurlaila; Hendra Harmain (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
The study aims to reveal the relationship variable sources of Islamic law as the primary basis in running financial accountability and accounting as a tool of accountability and presenting accurate information. As the cornerstone of financial accountability must be implemented, the command set in surah Al-Baqarah 282 which is about an order to make the process of accounting for each transaction. By using a sample of 32 mosques in the eastern coast of Sumatra as respondents, 70 question questionnaire. Sources of Islamic law and accounting as independent variables try to see to what extent can affect and realize the achievement of financial accountability/ financial reporting as the dependent variable. The results showed that the sources of Islamic law and accounting instrumental in realizing the financial reporting accountability accountable and transparent. Accounting is more dominant in influencing the accountability/ financial reporting. Statistically, the source of Islamic law and can explain about the liability of accounting / financial reporting amounted to 86.9%.